Virological and Serological Surveillance of Avian Influenza Virus in the Birds of Grenada - Sabarinath, Arathy; Sabarinath, Gopalakrishnan P.; Tiwari, Keshaw P.; Kumthekar, Sachin M.; Thomas, Derek; Sharma , Ravindra N. (International Journal of Poultry Science, 2011)
The zoonotic potential of the circulating influenza subtypes in avian species underscore the importance of surveillance of influenza virus in the avian population. So far there is only one published study in the Caribbean region on the presence of Avian Influenza Virus (AIV) in Barbados. A screening approach based on blood and cloacal and tracheal swabs to study the prevalence of influenza A in the avian population of Grenada was carried out in 2009-2010. We collected 230 blood samples and 230 mixed tracheal and cloacal swabs from backyard chicken (143), ducks (45), turkey (10), guinea fowl (1) and pigeon (31). Samples were screened by RT-PCR, embryo inoculation and ELISA for AIV. Neither AIV RNA was found by RTPCR nor could virus be isolated in embryonated eggs. 27 blood samples from backyard chickens were positive for AIV antibodies.